Media Pembelajaran Video Animasi Fisika dengan Microsoft Powerpoint - Didik Nur Huda; Santy Handayani (UNIVERSITAS INDRAPRASTA PGRI, 2021)
The Covid-19 pandemic requires teachers to be more creative and not technologically stuttering. One of the learning media is animated video that can be made with powerpoint. The subjects of this study were members of MGMP Fisika Kabupaten Serang. The teachers were given an explanation and surveyed their understanding of the PowerPoint animation video. The level of understanding of the teachers is quite good, reaching 63.6%.